ANXIETY IN ORAL PERFORMANCE TESTS: A CASE STUDY OF INDONESIAN LEARNERS - Valentinus Rido Rasmodjo (Universitas Katolik Indonesia Atma Jaya, 2011)
This study examined anxiety experienced by students before an oral performance test, the relationship between the anxiety and their test performance, and strategies they applied to reduce the anxiety. The participants were 107 Indonesian students who enrolled the English speaking classes. This study revealed that the students did not experience a high level of anxiety before the oral performance test. There was not a very significant relationship between anxiety and their score in the performance test. Finally, some strategies to cope the anxiety were also discussed. Keywords: anxiety, oral performance test, strategies, and scores